2019
DOI: 10.1111/jhn.12651
|View full text |Cite
|
Sign up to set email alerts
|

Healthy eating interventions in adults living with and beyond colorectal cancer: a systematic review

Abstract: Background Rates of cancer survival are increasing, with more people living with and beyond cancer. Lifestyle recommendations for cancer survivors are based largely on extrapolation from cancer prevention recommendations. The present study aimed to systematically review the literature on randomised controlled trials (RCTs) focusing on healthy eating interventions in people with colorectal cancer (CRC). Methods A structured search of electronic databases was conducted in March 2018 using medical subject heading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Other researchers have been pioneers in cancer survivorship research emphasising the promotion of long-term health for cancer survivors [60], developed an evidence based interventions primarily for breast cancer survivors [61,62] and demonstrated positive changes in dietary and other health outcomes in several RCTs [8,21,23]. In colorectal cancer, only a few trials have been published to date [63,64], and many gaps exist within the evidence base [8]; therefore, more research is required in this cancer population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers have been pioneers in cancer survivorship research emphasising the promotion of long-term health for cancer survivors [60], developed an evidence based interventions primarily for breast cancer survivors [61,62] and demonstrated positive changes in dietary and other health outcomes in several RCTs [8,21,23]. In colorectal cancer, only a few trials have been published to date [63,64], and many gaps exist within the evidence base [8]; therefore, more research is required in this cancer population.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed RCT aims to evaluate the feasibility of conducting a fully powered trial for the HEAL ABC intervention. This study has been developed from previous research within the area of CRC survivorship including qualitative work [18,25], discrete choice experiment [24] and systematic reviews [19,63]. The proposed study attempts to address areas where research is lacking in the evidence base identified by a Cochrane Systematic review on dietary interventions for cancer survivors [8].…”
Section: Discussionmentioning
confidence: 99%
“…Diet may continue to be a focus through management of malnutrition, symptom management or being considered along with lifestyle with the aim of influencing recurrence. Intervention studies to date in people following treatment for gastrointestinal cancer have failed to demonstrate that changes to body composition, dietary intake or physical activity can influence the risk of recurrence or overall survival (58) . Observational studies have suggested that body increased waist circumference, higher BMI and low adherence to the World Cancer Research Fund; Dietary Guidelines for Primary Prevention are associated with poorer global health status in people following treatment for colorectal cancer (59,60) .…”
Section: Diet After Treatment For Gastrointestinal Cancermentioning
confidence: 99%
“…Meta-analyses as well as reviews have shown their influence on physical and mental health [ 1 , 2 ]. For example, reviews and different studies have found correlations between healthy diets and cardiovascular, metabolic (e.g., Diabetes mellitus), or oncological diseases [ 3 , 4 , 5 ]. Health-related and preventive behaviors such as physical activities are also recommended by international societies and studies, which have shown positive effects on disease prevention [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%